A Clustering Algorithm Based on Mobility Properties in Mobile Ad Hoc Networks. (1st June 2015) - Oh, Young-jun; Lee, Kang-whan
Abstract : We propose a context-awareness routing algorithm—the DDV- (Dynamic Direction Vector-) hop algorithm—in mobile ad hoc networks. The existing algorithm in MANET has the limitations of the dynamic network topology and the absence of network expandability of the mobility of nodes. The proposed algorithm performs cluster formation for the base station using the range of direction and threshold of velocity. We calculate the exchange of the cluster head node probability using the direction and velocity for maintaining cluster formation. The DDV-hop algorithm, a probabilistic routing protocol for such networks, is proposed and then compared to the earlier presented algorithms through simulations. The simulations are conducted on a number of clusters, network areas, transmission ranges, and velocity of nodes in mobile networks. Our results suggest that the DDV-hop algorithm demonstrates efficiency of eventual delivery and maintains the proper number of clusters and cluster members regardless of topology changes with a lower communication overhead in several interesting environments.